2012
DOI: 10.2460/ajvr.73.11.1765
|View full text |Cite
|
Sign up to set email alerts
|

Associations among serum N-terminal procollagen type III concentration, urinary aldosterone-to-creatinine ratio, and ventricular remodeling in dogs with myxomatous mitral valve disease

Abstract: In dogs with MMVD, echocardiographic indicators of left ventricular remodeling appeared to be associated with a decrease in serum concentration of a marker of collagen type III turnover and an increase in urinary aldosterone concentration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
18
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 46 publications
6
18
0
Order By: Relevance
“…Via its actions on the mineralocorticoid receptor, aldosterone promotes fluid retention, leading to volume-overload and stimulates myocardial fibrosis [12]. Urinary aldosterone to creatinine ratio (UAC) is associated with the rate of change of left ventricular size in dogs with MMVD, suggesting that aldosterone production increases during periods of active remodelling [13]. Spironolactone is a mineralocorticoid receptor antagonist that has been shown to prolong survival times in dogs with advanced MMVD and CHF secondary to MMVD, when given in combination with standard therapy [14].…”
Section: Introductionmentioning
confidence: 99%
“…Via its actions on the mineralocorticoid receptor, aldosterone promotes fluid retention, leading to volume-overload and stimulates myocardial fibrosis [12]. Urinary aldosterone to creatinine ratio (UAC) is associated with the rate of change of left ventricular size in dogs with MMVD, suggesting that aldosterone production increases during periods of active remodelling [13]. Spironolactone is a mineralocorticoid receptor antagonist that has been shown to prolong survival times in dogs with advanced MMVD and CHF secondary to MMVD, when given in combination with standard therapy [14].…”
Section: Introductionmentioning
confidence: 99%
“…We aimed to exclude other such disease processes by ensuring that thorough physical examinations and histories were performed and performing screening tests on HSDM cats when appropriate, including serum total T4 concentration and abdominal imaging (eg, ultrasound examinations or computed tomography), as well as by following the progress of cats after their initial visits. Two previous studies demonstrated use of PIIINP concentration in dogs . Future studies assessing the impact of common disease processes and varying physiological states in the cat also are indicated, but were beyond the scope of our current study.…”
Section: Discussionmentioning
confidence: 94%
“…Two previous studies demonstrated use of PIIINP concentration in dogs. 40,41 Future studies assessing the impact of common disease processes and varying physiological states in the cat also are indicated, but were beyond the scope of our current study. Using diabetic cats as a control group likely makes the findings of our study stronger, given the known high prevalence of comorbidities in diabetic cats, 42 all with potential to affect PIIINP concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Although in‐house stability testing showed prolonged stability of serum aldosterone, sample degradation in plasma remains a possible cause of these low concentrations. Alternative explanations include the chronicity of benazepril treatment (16‐62 days, with median 33 days) and the possibility for reduced RAAS activation in the chronic, stable phase of CHF . Despite this, both treatments containing BNP1‐32 appeared to demonstrate an initial suppression and then a rise in aldosterone concentrations on visual inspection of Figure .…”
Section: Discussionmentioning
confidence: 99%